Scalable Biomimetic Coaxial Aligned Nanofiber Cardiac Patch: A Potential Model for “Clinical Trials in a Dish” - Kumar, Naresh; Sridharan, Divya; Palaniappan, Arunkumar; Dougherty, Julie A.; Czirok, Andras; Isai, Dona Greta; Mergaye, Muhamad; Angelos, Mark G.; Powell, Heather M.; Khan, Mahmood (Frontiers in Bioengineering and Biotechnology, 2020)
Recent advances in cardiac tissue engineering have shown that human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) cultured in a 3-D micro-environment exhibit superior physiological characteristics compared with their 2-D counterparts. These 3-D cultured hiPSC-CMs have been used for drug testing as well as cardiac repair applications. However, the fabrication of a cardiac scaffold with optimal biomechanical properties and high biocompatibility remains a challenge. In our study, we fabricated an aligned PCL-Gelatin coaxial nanofiber patch using electrospinning. The structural, chemical and mechanical properties of the patch were assessed by SEM, ICC, FTIR-spectroscopy, and tensile testing. hiPSC-CMs were cultured on the aligned coaxial patch for two weeks and their viability (LDH assay), morphology (SEM, ICC), and functionality (calcium cycling, MEA) were assessed. Furthermore, particle image velocimetry (PIV) and multielectrode array (MEA) were used to evaluate the cardiotoxicity and physiological functionality of the cells in response to cardiac drugs. Nanofibers patches were comprised of highly aligned core-shell fibers with an average diameter of 578 ±184 nm. Acellular coaxial patches were significantly stiffer than gelatin alone with an ultimate tensile strength of 0.780 ± 0.098 MPa but exhibited gelatin-like biocompatibility. Furthermore, hiPSC-CMs cultured on the coaxial patch were elongated and rod-shaped with well-organized sarcomeres, as observed by cardiac Troponin-T and α-Sarcomeric actinin expression. Additionally, hiPSC-CMs cultured on these coaxial patches formed a functional syncytium evidenced by the expression of Cx-43 and synchronous calcium transients. Moreover, MEA analysis showed that the hiPSC-CMs cultured on aligned patches showed an improved response to cardiac drugs like isoproterenol (ISO), verapamil (Vera), and E4031, compared to the corresponding 2-D cultures. Overall, our results demonstrated that an aligned, coaxial 3-D cardiac patch can be used for culturing of hiPSC-CMs. These biomimetic cardiac patches could further be used as a potential 3-D in vitro model for “clinical trials in a dish” and for in vivo cardiac repair applications for treating myocardial infarction.